Pipe-line transportation of heavy oil-in-water emulsion - Vickneswaran, Nagaratnam (2010)
The diverse factors affecting the viscosity of a viscous crude oil-in-water emulsion for pipeline transportation were studied. The factors that are taken into account is effect of oil content, type and concentration of the surfactant, and speed of mixing, Agent in water method is used in the preparation of oil in water emulsions. The oil content ratio used in this study is 50-50, 70-30, and 90-10 by volume. Different surfactants, namely Triton X-100, Span 80 and Tween 80 are used to determine the best surfactant to emulsify heavy oil. The speed of mixing used in this study is 1000rpm, 1500rpm and 2000rpm. This study is conducted in room temperature. Amine functional group demulsifier are used to study the destabilization of heavy oil in water emulsions. The demulsifier used in this study is hexylamine and dioctylamine. The viscosity of the oil in water emulsion was found to decrease as the oil content of the emulsion decreased, and the speed of mixing decreased. The stability of the crude oil-in-water emulsions increases as the oil content of the emulsions increases, the surfactant concentration increases, and the speed of mixing increases. Hexylamine remove more water over time in the destabilization process. Hence, hexylamine is a better demulsifier than dioctlamine. From this research it can be concluded that oil in water emulsion method can reduce the viscosity of heavy crude oil greatly.